Community acquired pneumonia: a cost-of-illness analysis in Greece - Panagiota Naoum; Kostas Athanasakis; Ilias Kyriopoulos; Adamantia Liapikou; Michail Toumbis; John Kyriopoulos (James Cook University, 2020)
Introduction: Community acquired pneumonia (CAP) is an acute respiratory infection with high clinical and economic burden, especially when hospitalisation is required. The present study aimed to assess the mean direct cost per CAP outpatient and inpatient care in Greece, in the absence of previous estimates. Methods: A retrospective analysis of patients at a tertiary hospital, treated between October 2015 and March 2016, was conducted. Resource use data for inpatients and outpatients were collected (diagnostic tests, medication, physician visits and length of hospitalisation, where applicable). Cost calculations followed a third party payer perspective. Additionally, two regression models were employed to identify the determinants of hospitalisation and the main drivers of inpatient and outpatient cost. Results: Overall, 149 inpatients and 100 outpatients were included in the analysis. Mean hospitalisation duration was 11.35 days (standard deviation (SD)=9.71 days). Mean direct cost per patient was €110.64 (SD=€58.23) and €7406.56 (SD=€12,124.93) for outpatient and inpatient cases respectively. (At the time period for the study, €1.00 was approximately A$1.50.) The main inpatient cost driver was hospitalisation (94.97%), followed by medication (3.30%) and diagnostic tests (0.87%). For outpatients, key cost drivers, in order of magnitude, were prescribed medication (38.84%), diagnostic tests (33.51%) and physician visits (17.54%). The regression analyses showed that the probability of hospitalisation increases with age and number of symptoms, whereas average cost is mainly influenced by gender, duration and number of symptoms, and the presence of comorbidities. Conclusion: The results indicate that, in Greece, CAP is accompanied by a significant economic burden, mainly attributable to hospitalisation. Interventions toward reducing the influence of contributors to the incidence and probability of hospitalisation are essential from a clinical and policy perspective. Also, the association of symptoms - in terms of number and duration - and age with hospitalisation probability and costs highlights that special attention should be given to the high risk groups of the population, such as the elderly and the rural residents, both in terms of preventive and therapeutic services.